IMPLEMENTASI MANAJEMEN OPERASIONAL ZAKAT PRODUKTIF DALAM PERSPEKTIF EKONOMI ISLAM - Widjanarko, Irsyad Kurniawan; Hafidz, Muhammad Bobby; Jalil, Muhammad; Baehaki, Ahmad (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
The implementation of productive zakat operational management from an Islamic economic perspective has the aim of optimizing the potential of zakat in caring for mustahik so that it can provide sustainable improvement in their lives. The author uses the literature study research method in the research. Zakat has an important role as a potential source of funds to alleviate poverty and can be working capital for poor people to create employment opportunities, so that they can generate income and meet their living needs. From an Islamic economic perspective, zakat management involves the principles of justice, transparency and accountability which function to ensure zakat funds are right on target and provide a significant positive impact in eliminating poverty. Productive zakat funds are not funds that can be directly consumed by mustahik, but rather funds that can be used by mustahik to become entrepreneurs and improve their quality of life but can also provide support for the sustainability of mustahik's lives in the future until they turn into muzaki. This goal is in line with the aim of zakat as an instrument of fair redistribution of wealth, as well as being able to move the community's economy in accordance with sharia principles. Keywords : Islamic Economics, Management Strategy, Operational Management,  Productive Zakat